Exploring adolescents' mental health in Kampala, Uganda in the context of COVID-19: a mixed methods study - Mbithi, Gideon; Sarki, Ahmed; Mabrouk, Adam; Odhiambo, Rachel; Namuguzi, Mary; Atukwatse, Joseph; Kabue, Margaret; Mulupi, Stephen; Abubakar, Amina (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundUrban areas, particularly in developing nations like Uganda, face heightened risks due to poverty, unemployment, and environmental challenges, intensifying the vulnerability of urban youth to poor mental health. This study aims to determine the psychological well-being of adolescents and to assess the risks and associated factors of mental health problems among adolescents in the context of COVID-19 pandemic in Kampala City, Uganda.MethodsWe conducted a cross-sectional survey of 500 adolescents aged 13–19 years residing within the five divisions of Kampala City, Uganda. We utilized standardized psychological assessment tools including the Patient Health Questionnaire, Generalized Anxiety Scale, to assess severity of depression and anxiety levels among the adolescents. A logistic regression model was used to evaluate the correlates associated with depression and generalized anxiety disorders. Variables with a p-value <0.25 in the univariate model were included in the multivariable regression model. Subsequently, we conducted a qualitative study using semi-structured interview guides through focused group discussions, and key informant interviews with teachers, parents, representatives of civil society organizations, and religious leaders. Qualitative data were analyzed using a thematic analysis approach.ResultsThe prevalence of depression was relatively higher among out-of-school adolescents at 21.5% compared to school-going adolescents at 14.0%. Furthermore, out-of-school adolescents had significantly higher anxiety scores when compared to their school-going counterparts (17.5% vs. 10.3%) respectively. Key factors identified associated with poor mental health include loneliness, being out of school, COVID-19, and familial conflicts.DiscussionThis study highlights the impact of the COVID-19 pandemic on the mental well-being of adolescents in Kampala, Uganda. The reported prevalence of depression and anxiety, particularly among out-of-school adolescents, underscores the urgent need for targeted interventions in this vulnerable population. Investing in the mental well-being of Ugandan adolescents is paramount for fostering resilience and ensuring long-term success, especially in marginalized urban settings.